P46 Blood lactate may be superior to child-pugh score for identifying futility in patients undergoing salvage TIPSS. (28th September 2020) - Naik, Keval; Cacciottolo, Tessa; See, Teik Choon; Leithead, Joanna A
Abstract : As per the recently published British Society of Gastroenterology guideline, salvage transjugular intrahepatic portosystemic stent-shunt (TIPSS) is not recommended where the Child-Pugh score is >13 because of futility; however data is sparse, and case series have largely predated the use of covered stents and the modern era of Intensive Care management. Aim: We sought to determine whether Child-Pugh score >13 is indeed a marker of futility in patients undergoing salvage TIPSS, and whether alternative markers are superior. Methods: This was a retrospective single centre study of 37 consecutive patients who underwent salvage TIPSS between 12/2014 and 03/2020. Salvage was defined as gastro-oesophageal variceal bleeding refractory to endoscopic and drug therapy. Results: The median preTIPSS Child-Pugh score was 11: 3%, 38% and 59% of patients were Child-Pugh class A, B and C, respectively. The absolute 6-week mortality rate was 32%; whilst 59% had died by 1-year post TIPSS. There was no difference in Child-Pugh score (10 vs 11.5; median, p=0.360) or Child-Pugh grade (60% vs 58%, Child-Pugh C, p=0.923) when patients who did or did not survive to 6 weeks were compared. Six patients had a preTIPSS Child-Pugh score of >13: 3 died within 6-weeks; one was considered for transplantation but declined because of recidivism risk, dying at 251 days; one recovered and died unexpectedly at 131 days; and one is still alive at 684 days of followup. There was no association between preTIPSS MELD (22 vs 16; median, p=0.151), APACHE II (17 vs 14; median, p=0.151), SOFA (10 vs 7; median, p=0.124) or CLIF-C ACLF (54 vs 50, median; p=0.095) scores preTIPSS and 6 week mortality. Amongst patients with ACLF, 43% did not survive beyond 6 weeks compared with 19% without ALCF (p=0.121). Blood lactate immediately preTIPSS was higher in patients who died by 6-weeks (2.5 vs 1.5 mmol/l; median, p=0.008). The 6-week mortality rate was 12%, 40% and 75% for patients with a lactate of <1.8, 1.8–2.5, and ≥2.6 mmol/l, respectively (p=0.002). Seven of 8 patients with a lactate ≥2.6 mmol/l had died by 1-year with a median time to death of 15 (range 1–52) days. Conclusion: Child-Pugh score >13 is not a definitive indicator of short term mortality in patients undergoing salvage TIPSS. Instead blood lactate may be a superior predictor of futility.